Pakikipagkapwa-damdamin accompanying survivors of disasters - Carandang, Maria Lourdes Arellano (Bookmark, 1996)
This is a handy book that describes the multi-level psychosocial interventions of an Ateneo team of psychologists with survivors of the 1990 killer quake and other natural disasters. It is written in a descriptive, narrative and personal rather than a prescriptive tone. It uses the psychological approach to examine the phenomenological world of survivors.